The Influence Of Price Perception, Lifestyle, And Customer Reviews On The Decision To Purchase Somethinc Products In Tiktok Shop - Febry Lodwyk Rihe Riwoe; Risya Shakira Syaharani; Mumuh Mulyana (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The rapid growth of social commerce platforms such as TikTok Shop has reshaped consumer purchasing patterns, especially among younger generations. In October 2023, the Indonesian government temporarily restricted TikTok Shop’s transactional activities due to concerns over its potential impact on local MSMEs, before allowing it to resume operations through a joint integration with Tokopedia in 2024. This regulatory shift highlights the importance of understanding both psychological and digital factors that influence purchasing decisions within interactive online platforms. This study aims to examine the influence of price perception, lifestyle, and customer reviews on the purchasing decisions of Somethinc products via TikTok Shop. A quantitative research method was employed using probability sampling techniques, and data were analyzed using SmartPLS 4.0. The results indicate that price perception, lifestyle, and customer reviews each have a positive and significant effect on purchasing decisions. The model demonstrates an R-Square value of 0.713, suggesting that the three variables explain 71.3% of the variance in purchasing decisions. Theoretically, the findings reinforce the Theory of Planned Behavior and Signaling Theory, emphasizing that consumer perceptions and external digital stimuli—such as online reviews and brand credibility—affect intention-based decision-making. Managerially, companies are advised to enhance price transparency, align with consumer lifestyle trends, and leverage interactive review features and live-commerce strategies. Future research should consider additional moderating variables such as customer engagement or brand trust and expand the demographic coverage.   Keywords: price perception, lifestyle, customer review, purchase decision, tiktok shop, digital marketing